Impact of China-Pakistan Economic Investment on Volatility of Stock Exchanges in Pakistan and Shanghai - Natacha Silva; Dos-Santos, M.J.P.L. (Human Factors in Management and Leadership, Vol. 92, 2023, 49–54, 2023)
This paper aims to analyze the impact of the China-Pakistan Economic Corridor on the volatility of the Pakistan Stock Exchange and Shanghai Stock Exchanges, namely, to explore the pre and post-impact China investments in Pakistan in the energy sector on the stock exchanges of the respective countries. The methods used include an econometric analysis, and univariate statistical analysis, from February 2010 to January 2020. The results present a significant difference in volatilities of the pre and post-returns of both indices. Stock prices increased post-CPEC announcement in Pakistan, and there was a growth in the stock market. However, the mean return post-CPEC announcement is relatively lower than Pre-announcement tenure, combined with higher volatility. It shows small investors’ underconfidence. The conclusion is the significant economic advantages of CPEC to PK.